Journal of Fundamental and Applied Sciences is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License. Libraries Resource Directory. We are listed under Research Associations category. FLOWERING PLANTS PREFERRED BY NATIVE WILD BEES (HYMENOPTERA, APOIDEA, APIFORMES) IN THE ALGERIAN LITTORAL REGION - L, . Bendifallah1; F., J. Ortiz-Sánchez2 (جامعة الوادي university of eloued, 2018)
This study considered the plant floral resources visited by native wild and honey bees in Algiers (northern Algeria). Three botanical families accounted for almost 2/3 of all visits: Asteraceae (44.1%), Boraginaceae (15.3%) and Brassicaceae (13%). Plants in other families were visitedless frequently (e.g.Ranunculaceae (0.1%)). At the species level, the most frequently visited plant was Anchusa azurea (Boraginaceae), reaching 15.2% of the total bee visitation. Our work showed that Apis mellifera Linnaeus, 1758 is, typically, a polylectic species and that the majority of solitary bees exhibited the more specialised trait of oligolectics. The narrowest trophic niche varied between 0.01 and 0.06 bits for Halictusrufipes (Fabricius, 1793), Halictus scabiosae (Rossi, 1790) (Halictidae), Osmia pinguis Pérez, 1895 and Osmia tricornis Linnaeus, 1811 (Megachilidae)
artical
Keywords: Wild bees, floral choices, natural habitat, northern of Algeria